The Expression and Significance of Immunoglobulin Free Light Chain in the Patients with Allergic Rhinitis and Nonallergic Rhinitis. Issue 4 (July 2014) - Meng, Cuida; Sha, Jichao; Li, Lin; An, Lifeng; Zhu, Xuewei; Meng, Xun; Zhu, Dongdong; Dong, Zhen
Background: Inflammation has been shown to be an integral component of allergic rhinitis (AR). However, there is no n worth debate regarding this fact in nonallergic rhinitis (NAR). Some studies have suggested that exclusion of inflammation is indicative of NAR and other studies have indicated that most of the NAR patients have some degree of inflammation. Recently, it has been shown that the level of immunoglobulin free light chains (IgFLCs) in serum is increased in some autoimmune diseases and airway inflammation. This study was designed to show whether IgFLC is associated with non–IgE-mediated rhinitis to reveal the relationship between the expression of IgFLC and activation of mast cells and eosinophils. Methods: Thirty patients with IgE-mediated AR and 30 patients with NAR and 30 healthy persons as control were involved this study. The total IgE, IgFLC, eosinophil cationic protein (ECP) and mast cell tryptase (MCT) in serum, and nasal secretions were assayed, respectively. For identifying the expression cells of IgFLC in nasal mucosa, the immunohistochemical (IHC) staining for kappa-FLC, gamma-FLC, ECP, and MCT were performed on 30 specimens. Meanwhile, the mRNA expression of kappa-FLC, gamma-FLC, and MCT was determined by real-time quantitative polymerase chain reaction. Results: IgFLCs (kappa/lambda) levels in serum and nasal secretion were significantly increased in AR patients and NAR patients. The ECP and MCT levels in serum and nasal secretion were significantly enhanced in AR and NAR patients when compared with healthy control subjects (p < 0.01). There was a positive correlation between IgFLC (kappa/lambda) and MCT n nasal secretion of patients with NAR, but only IgFLC (kappa-FLC was associated with MCT in AR. There was no correlation between IgFLC and ECP in nasal secretion. In serum expression level, there was a positive correlation between IgFLC (kappa) and ECP in AR or IgFLCs (lambda) and ECP in NAR. IHC staining showed that FLC + cells were significantly increased in AR and NAR mucosa, kappa-FLC was mainly expressed in epithelial cells, and lambda-FLC was mainly expressed in subepithelial cells. Double immunofluorescence staining showed that the expression of lambda-FLC was mainly localized in mast cells in NAR nasal mucosa (45%). Conclusion: These findings suggest strongly that IgFLC may play an important role in inducing local nasal mucosa inflammation especially those in AR and NAR.